Biopesticides for sustainable agriculture: feasible options for adopting cost-effective strategies - Fenibo, Emmanuel O.; Matambo, Tonderayi (Frontiers in Sustainable Food Systems, 2025)
Biopesticides have emerged as a central focus in contemporary policy and scientific discourse due to their strong alignment with green chemistry, One Health initiatives, the Sustainable Development Goals (SDGs), and sustainable agriculture. Beyond their established role in integrated pest management (IPM), they serve as a pivotal driver in building resilient agricultural systems. However, their wider adoption is constrained by technical limitations and the high costs associated with refined formulations. This review aims to identify types and strategies of biopesticides that are both cost-effective and suitable for sustainable agriculture. Drawing on multiple case studies across diverse agroecological zones, the analysis reveals that cost-effective biopesticides are critical for advancing IPM in traditional and smallholder farming systems, while branded formulations predominantly benefit large-scale farms with greater economic capacity. Emphasis is placed on the utilization of readily accessible biopesticides, including pesticidal plants, natural enemies, entomopathogenic nematodes, and botanical extracts and seed/seedling treatments, which collectively mitigate pest pressure, reduce reliance on chemical pesticides, and enhance crop yields within a structured progression described as the IPY trend. This trend underscores the interlinked dynamics of infestation levels, pesticide consumption, and crop productivity under cost-effective, biopesticide-driven IPM. Within this low-tech and high-tech classification framework, persistent controversies and the misconception that developing nations, long reliant on traditional agricultural technologies, lack awareness of biopesticides can be systematically examined and addressed, thereby facilitating informed policy decisions and optimized implementation strategies.